Militant Democracy and Its Critics - Malkopoulou, Anthoula; Kirshner, Alexander (Edinburgh : Edinburgh University Press, 2019)
Can defensive efforts that curtail rights of participation of antidemocratic movements be consistent with democratic values? In this collection of essays, scholars from across politics, philosophy and law address the unresolved practical and theoretical questions concerning democracy and extremism.
ELEVEN Militant Democracy as an Inherent Democratic Quality -- References -- Index
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Democracy; Populism; Political parties; Radicalism; World politics -- 21st century; Populisme; Radicalisme; Politique mondiale -- 21e siècle.; radicalism; Democracy; Political parties; Populism; Radicalism; World politics; 2000-2099